DIGITAL LITERACY: DOES IT AFFECT THE LEARNING OUTCOMES OF MADRASAH IBTIDAIYAH STUDENTS? - Adit Yuliani; Anas Salahudin; Inne Marthyane Pratiwi (PEDAGOGIA, 2022)
The ease of Science and Technology must be balanced with digital literacy skills because it is one-factor affecting student learning achievement. Digital literacy functions to have the ability to access, manage, understand, and evaluate information safely and quickly through digital technology to become wiser. This study aims to look at students' digital literacy skills and learn achievement and determine how much influence digital literacy has on student learning achievement. The research method used is a correlation with a quantitative approach, and the sample is taken from classes IV, V, and VI, with as many as 50 students. The data collection technique used is a questionnaire for digital literacy and documentation for learning achievement. Then the data analysis technique used the product-moment correlation test. The results of this study indicate that students are good at understanding digital literacy. Students' understanding of digital literacy on internet skills, such as utilizing digital technology to find information and learning resources. There is a significant positive relationship between digital literacy and learning achievement, and it is obtained that an r count of 0.440 is included in the medium category. It is shown that digital literacy skills influence 19.36% of student learning achievement, and the remaining 80.64% is influenced by other factors that are not related to this study.